Functional Starch and Applications in Food (Springer Singapore, 2018)
This book discusses functional starch and its applications in food, focusing on starches with possible health benefits or novel applications. Covering slowly digested starch, resistant starch, porous starch, starch microemulsions, microcrystalline starch and noncrystallization starch and their applications, this book provides a valuable reference for graduate students and research professionals in the food and chemical industries. .